Effects of Persistent and Bioactive Organic Pollutants on Human Health - Carpenter, David O. (Wiley, 2013)
BExamines what we know about the relationship between organic chemicals and human disease/b/ Organic chemicals are everywhere: in the air we breathe, the water we drink, and the food we eat. They are also found in a myriad of common household and personal care products. Unfortunately, exposure to some organic chemicals can result in adverse health effects, from growth and developmental disorders to cancer and neurodegenerative diseases. This book examines how organic chemicals affect human health. It looks at the different diseases as well as how individual organ systems are affected by organic chemicals. iEffects of Persistent and Bioactive Organic Pollutants on Human Health/i begins with an introductory chapter explaining why we should care about organic chemicals and their effect on human health. Next, the authors address such important topics as:ulliBurden of cancer from organic chemicals/liliOrganic chemicals and obesity/liliEffects of organic chemicals on the male reproductive system/liliOrganic chemicals and the immune system/liliIntellectual developmental disability syndromes and organic chemicals/liliMental illness and exposure to organic chemicals/li/ul The book ends with an assessment of how much human disease is caused by organic chemicals. Chapters have been contributed by leading international experts in public and environmental health and are based on the latest research findings. Readers will find that all of the contributions are clear and easy to comprehend, with extensive references for further investigation of individual topics. iEffects of Persistent and Bioactive Organic Pollutants on Human Healthi is recommended for students and professionals in medicine as well as public and environmental health, bringing them fully up to date with what we know about the relationship between organic chemicals and human health.
Polybrominated Biphenyl Ethers (PBDEs) and T2DThrifty Gene Hypothesis and POPs; POPs and Glycemic Control among Diabetic Patients; Dietary Interventions in T2D; Summary; References; CHAPTER 6: Mechanistic Basis for Elevation in Risk of Diabetes Caused by Persistent Organic Pollutants; Introduction; Diabetes; POPs: Novel Diabetogenic Factors; POPs and Diabetes: Mechanistic Basis; AhR; CAR and SXR; Challenges and Perspectives; References; CHAPTER 7: Cardiovascular Disease and Hypertension; Introduction; Animal Studies and Laboratory Evidence.
Includes bibliographical references and index.
Print version record.
Keywords: Bioactive compounds -- Toxicology; Organic compounds -- Toxicology; Persistent pollutants -- Health aspects; Ecotoxicology; Organic Chemicals -- adverse effects; Organic compounds -- toxicology; SCIENCE -- Chemistry -- Industrial & Technical; Electronic books